Refinement of the Catalyst Backbone of Chiral Intramolecular Silicon–Sulfur Lewis Pairs: Improved Enantioselectivity in the Diels–Alder Reaction of Cyclohexa‐1, 3‐diene and Chalcone Derivatives. Issue 23 (3rd May 2018) - Shaykhutdinova, Polina; Kemper, Sebastian; Oestreich, Martin
Abstract : The preparation and NMR spectroscopic characterization of a family of axial chiral, sulfur‐stabilized silicon cations is reported. These silicon Lewis acids have been applied as catalysts in difficult enantioselective Diels–Alder reactions of cyclohexa‐1, 3‐diene and representative chalcone derivatives. To gain better understanding of the relevant structural elements in these catalysts, their silepine backbone and the aryl thioether group have been systematically modified. These efforts have led to an improved catalyst that induces 53 % ee for chalcone and even 65 % ee for a more hindered derivative. These cyclohexa‐1, 3‐diene Diels–Alder reactions are endo selective. However, the corresponding cyclopentadiene Diels–Alder reactions predominantly yield the exo cycloadducts with no enantioinduction. Abstract : Step by step . A new, structurally modified silicon cation intramolecularly stabilized by a sulfur donor catalyzes challenging Diels–Alder reactions of cyclohexa‐1, 3‐diene and chalcone derivatives with improved enantiomeric excesses. The endo selectivity typically observed is inverted to exo with cyclopentadiene, and no enantioinduction is obtained.